(untitled) (Research, Society and Development, 2021)
Among the livestock activities developed in Rondônia, the creation of small ruminants stands out with great importance. One of the difficulties of livestock in the region is the quality and availability of quality food. In this way, technologies such as hydroponic green forage cultivation appear as an alternative to increase animal production. Thus, the objective of the research was to evaluate the production of green matter/dry matter and chemical composition of corn and soy hydroponic, in inert substrates and N in topdressing. The research was conducted at the Federal Institute of Education Science and Technology of Rondônia, Campus Cacoal, RO, from March to July 2018 in a greenhouse. The experimental design was completely randomized, a 2x3 factorial scheme, consisting of 6 treatments with 4 replications, totaling 24 plots. The plots had a useful area of 1,0 x 1,0 x 0,04 m in depth. Chlorophyll, dry matter and chemical-bromatological analyzes were performed on the 15th day after sowing. The results obtained demonstrated that the relative chlorophyll content in the leaves does not change with the addition of nitrogen in top dressing in hydroponic corn at 15 days after sowing. The contents of protein, ash and ether extract, increased with the inclusion of 25% and 50% of soy in consortium with corn. The consortium between corn and soy did not alter the production of green and dry matter in a hydroponic system with rice straw.